Penanaman Karakter Disiplin Dan Kerja Keras Pada Pekerja(Studi Kasus pada Pekerja Penyadap Karet di PT. PerkebunanNusantara IX TPH Dusun Karangnongko) - Widodo, Dito Dwi (2016)
This study aims to investigate the implementation, barriers, and efforts to overcome obstacles in the planting of character discipline and hard work on rubber tappers working in TPH Karangnongko Hamlet. The research data was gathered through informants, places, and documents. The study used a qualitative approach, data collection is done by observation, interview and documentation. Test the validity of the data with the triangulation of sources and techniques. The data analysis applying interactive models through data collection, data reduction, data presentation, and conclusion. The results of this study indicate that the character of discipline and hard work always instilled by the foreman to each worker in the rubber tappers TPH Karangnongko Hamlet. How foreman embed code of discipline and hard work to the worker rubber tappers through training tapping by special team of tapping on a bi-weekly basis, but it is also the assistance of a foreman at the time of carrying out the work, as well as impose a tri tapping (orderly start, orderly regulation, orderly pulung). This is always done to create workers who have the personality and character of discipline and hard work. Obstacles encountered in instilling character foreman discipline and hard work on the workers' lack of self-awareness on workers both in discipline and in the time to run the rule, they think about themselves and less concerned about the job. Efforts to overcome obstacles in the embed code of discipline and hard work that invites sharing together so that the existing problems can be resolved, as well as workers' rubber tappers expected to manage the time you have to be an existing target can be achieved with good, besides foreman giving advice workers to complete tasks and responsibilities well.